2017
DOI: 10.1097/md.0000000000006598
|View full text |Cite
|
Sign up to set email alerts
|

Delayed bilateral vocal cord paresis after a continuous interscalene brachial plexus block and endotracheal intubation

Abstract: Rationale:Recurrent laryngeal nerve block is an uncommon complication that can occur after an interscalene brachial plexus block (ISB), which may lead to vocal cord palsy or paresis. However, if the recurrent laryngeal nerve is blocked in patients with a preexisting contralateral vocal cord palsy following neck surgery, this may lead to devastating acute respiratory failure. Thus, ISB is contraindicated in patients with contralateral vocal cord lesion. To the best of our knowledge, there are no reports of bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…However, even if the catheter tip is in the correct position, local anesthetics may spread to the anterior part of the anterior scalene muscle, resulting in phrenic nerve block and dyspnea [16]. Similarly, when local anesthetics spread to the anterior part of the anterior scalene muscle through the prevertebral layer of the deep cervical fascia, the recurrent laryngeal nerve is blocked, resulting in hoarseness or cough reflex during drinking, or both [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, even if the catheter tip is in the correct position, local anesthetics may spread to the anterior part of the anterior scalene muscle, resulting in phrenic nerve block and dyspnea [16]. Similarly, when local anesthetics spread to the anterior part of the anterior scalene muscle through the prevertebral layer of the deep cervical fascia, the recurrent laryngeal nerve is blocked, resulting in hoarseness or cough reflex during drinking, or both [17].…”
Section: Discussionmentioning
confidence: 99%
“…LA toxicity is most often caused by inappropriate LA administration such as accidental intravascular injection or multiple injections. Toxic events can occur very fast following intravascular injection or can be delayed when absorbed from local tissue injection ( 8 ). Maximal safety dose of LA should not exceed the recommended dose because morbidity and mortality from LA significantly increases in higher doses.…”
Section: Discussionmentioning
confidence: 99%
“…Park H-S et al ( 8 ) showed that interscalene brachial plexus block (ISB) is contraindicated in patients with preexisting contralateral vocal cord palsy or paresis. Recurrent laryngeal nerve block is rare, but it is a possible complication of continuous ISB for shoulder surgery which may lead to acute respiratory failure in patients with contralateral vocal cord palsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, even if the catheter tip is in the correct position, local anesthetics may spread to the anterior part of the anterior scalene muscle, resulting in phrenic nerve block and dyspnea [16]. Similarly, when local anesthetics spread to the anterior part of the anterior scalene muscle through the prevertebral layer of the deep cervical fascia, the recurrent laryngeal nerve is blocked, resulting in hoarseness or cough reflex during drinking, or both [17]. Moreover, when local anesthetics spread to the cervical sympathetic ganglion, ptosis is observed as part of Horner’s syndrome [18].…”
Section: Discussionmentioning
confidence: 99%